Multifaceted Roles of Ferroptosis in Lung Diseases - Li, Yi; Yang, Ying; Yang, Yongfeng (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a new type of iron-dependent programmed cell death (PCD) that is characterized by the accumulation of intracellular iron, depletion of glutathione, inactivation of glutathione peroxidase and promotion of lipid peroxidation. Recently, accumulated studies have demonstrated that ferroptosis is highly associated with the development and progression of many lung diseases. In this review, we summarized the contribution of ferroptosis to the pathogenesis of lung diseases, including obstructive lung diseases (chronic obstructive pulmonary disease, asthma and cystic fibrosis), interstitial lung diseases (pulmonary fibrosis of different causes), pulmonary diseases of vascular origin (ischemia–reperfusion injury and pulmonary hypertension), pulmonary infections (bacteria, viruses and fungi), acute lung injury and acute respiratory distress syndrome, and lung cancer. We also discussed the therapeutic potential of targeting ferroptosis for these lung diseases.